2021
DOI: 10.1002/pat.5365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dimensionality of nanosized TiO2 embedded in regenerated cellulose beads as a portable catalyst for reusable decomposition system

Abstract: Free‐standing titanium dioxide (TiO2) nanowires (TNW) with great photocatalysis performances were formed by using a simple hydrothermal method. Pre‐cool rapid dissolution technique was used to dissolve cellulose, and the regenerated cellulose (RC) beads were used as a portable host for absorption and photocatalytic reaction. Comparisons were made between zero‐dimensional TiO2 nanoparticle (TNP) and one‐dimensional TNW, which both were mixed separately with dissolved cellulose and regenerated into spherical bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Evyan et al [26] suggested that the degradation system or structure can be developed as nanoparticle composites such as nanocellulose, polymer, ceramic, or other materials incorporated with nanoparticles. These systems or models are recyclable, reusable, cost-effective, and environmentally friendly and can achieve sustainability [41,42].…”
Section: Post-processing Recovery Of Photocatalyst In Pome Treatmentmentioning
confidence: 99%
“…Evyan et al [26] suggested that the degradation system or structure can be developed as nanoparticle composites such as nanocellulose, polymer, ceramic, or other materials incorporated with nanoparticles. These systems or models are recyclable, reusable, cost-effective, and environmentally friendly and can achieve sustainability [41,42].…”
Section: Post-processing Recovery Of Photocatalyst In Pome Treatmentmentioning
confidence: 99%